Public-private partnership in the sphere of physical culture and sports - O. I. Larina (Управление)
According to many expert estimates, the share of state spending on the creation and development of infrastructure projects in the field of physical culture and sports in Russia remains low, and in the current crisis does not cover the existing needs. In this regard, the question of improving the efficiency of the use of budgetary funds and stimulating the flow of private investment in this area remains open. The article analyzes the Russian practice of public-private partnership in the field of physical culture and sports. The forms of public-private partnership in the designated area, development trends and measures of state support existing both at the Federal and regional levels are investigated. Based on the analysis of the ongoing projects, as well as legal mechanisms that ensure the rights of investors in the Russian Federation, conclusions are drawn on the need to improve the mechanisms of support for public-private partnership in the field of physical culture and sports, while it is advisable to determine transparent and unambiguous criteria for the allocation of public funds. The main purpose of the article is to generalize and systematize the mechanisms of state support of private investment in the sports industry. Since the implementation of such projects should take into account the specifics of this area, the current trends in the development of entrepreneurship in the sports sector. It was concluded that the interaction of business in the field of physical culture and sports with the state should achieve a balance between the private interests of business and social objectives that are set and should be addressed in the interests of society